Effects of Dietary Fish Meal Replacement by Red Lentil Meal on Growth and Amino Acid Composition of Rainbow Trout (Oncorhynchus mykiss) - YÜRÜTEN ÖZDEMİR, Keriman; YILDIZ, Mustafa (Alinteri Zirai Bilimler Dergisi, 2019)
The purpose of this study was to determine the effects of replacing fish meal with red lentil meal (RLM) as an alternative plant protein source in diets for juvenile rainbow trout (10.14±0.04 g mean initial weight) on growth performance and amino acid composition of fish. Four iso-nitrogenous and iso-lipidic experimental diets were prepared to include 15% (RLM15), 20% (RLM20) and 25% (RLM25) of fish meal. At the end of the 60 day feeding trial, the highest mean individual weight gain (30.55±0.08 g) of fish was found in control group but not significantly different from RLM15. Crude protein level of whole body/fillet gradually decreased with increase in RLM percentages in the diets. Generally, essential amino acid (EAA) profiles of whole body/fillets reflected the dietary EAA profile. EAA profile of fish fed RLM15 diet was close to control group (P>0.05). However, lysine levels of fish decreased with increasing dietary RLM levels. RLM20 fed fish had the highest body contents of phenylalanine (P
Keywords: Rainbow trout; Nutrition; Fish meal; Red lentil meal; Amino acid; Growth; Agricultural, Veterinary and Food Sciences; Ziraat, Veterinerlik ve Gıda Bilimleri; 3. Good health